1985
DOI: 10.1093/infdis/152.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Parvoviral Infection in Humans

Abstract: Healthy adult volunteers were inoculated intranasally with human parvovirus obtained from an asymptomatic blood donor. One week after inoculation, intense viremia was observed in seronegative volunteers, accompanied by a mild illness with pyrexia, malaise, myalgia, itching, and excretion of virus from the respiratory tract. In the following week hematologic studies revealed reticulocytopenia with an associated slight drop in hemoglobin concentration, lymphopenia, neutropenia, and a drop in platelet counts. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
262
0
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 672 publications
(270 citation statements)
references
References 21 publications
5
262
0
3
Order By: Relevance
“…The virus is associated with arthropathies, hepatitis and various other syndromes and diseases. 1 Specific immunoglobulin M (IgM) and IgG antibodies are produced following experimental 2 and natural 3 B19 infection. Infection follows a biphasic clinical course: One week after intranasal inoculation with B19 in healthy adult volunteers, viraemia is detected in seronegative individuals accompanied by a mild illness with pyrexia, malaise, myalgia, itching, and excretion of virus from the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…The virus is associated with arthropathies, hepatitis and various other syndromes and diseases. 1 Specific immunoglobulin M (IgM) and IgG antibodies are produced following experimental 2 and natural 3 B19 infection. Infection follows a biphasic clinical course: One week after intranasal inoculation with B19 in healthy adult volunteers, viraemia is detected in seronegative individuals accompanied by a mild illness with pyrexia, malaise, myalgia, itching, and excretion of virus from the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal infection during pregnancy is associated with an increased risk of hydrops fetalis and fetal loss [2]. Experimental inoculation of human volunteers has shown that the major route of shedding of parvovirus B19 is respiratory secretions (saliva and nasal fluids), and that shedding occurs before the onset of symptoms [3]. IgG antibodies to parvovirus B19 can be detected in serum 2-3 weeks after acquisition of infection and last for life, providing immunity against re-infection [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery in 1975, parvovirus B19 (B19V) has been identified as the causative agent of a number of clinical conditions in humans (Anderson et al, 1985;Kurtzman et al, 1987). The spectrum of symptoms caused by B19V, including rash, arthralgia and transient aplastic crisis, are generally self-limiting in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%